Kajian Hukum Terkait Ketentuan Lese Majeste di Thailand dan Ketentuan Menyerang Kehormatan Presiden dalam UU No 1 Tahun 2023 - Rizki Pitri Julianti (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the legal provisions regarding the crime of lese-majesté in Thailand with the law regarding attacks on the honor of the President in Law Number 1 of 2023 in Indonesia, as well as their implementation and impact on freedom of expression and human rights. This research employs a normative legal study (juridical-normative) with a statutory approach. Furthermore, the nature of this research is descriptive-analytical. The data sources used in this normative juridical research are secondary data, which include primary legal materials, secondary legal materials, and tertiary legal materials.. First, this study discusses the description of the legal provisions regarding the crime of lese-majesté in Thailand which has very strict criminal sanctions, with provisions for violations against the President in Indonesia which are relatively looser, but still have the potential to limit freedom. Second, the differences and similarities in the application of the law in both countries lead to the use of the law as a tool to protect the dignity of the country's leaders, although with different levels of strictness. Third, the impact of the application of this law on freedom of expression and human rights shows that although both countries aim to protect the honor of the country's leaders, the application of the law can limit freedom of speech and opinion, which has the potential to restrict human rights. Overall, despite differences in the application of the law, both in Thailand and Indonesia, both face challenges in balancing protection of the honor of state leaders with human rights, especially freedom of expression.